STRATEGY OF BAHTSUL MASA'IL IN INCREASING THE CRITICAL REASONING OF SANTRI IN ASSUNIYAH KENCONG JEMBER ISLAMIC BOARDING SCHOOL - Arifin, Zainul; Alfarisi, Salman; Pramuja, Alvin Dian (An Natiq, 2024)
This study aims to analyze the effect of Bahtsul Masail management in improving the critical reasoning of santri at the Assuniyah Islamic Boarding School in Kencong, Jember. Bahtsul Masail is a discussion forum that emphasizes in-depth analysis of fiqh issues, expected to develop critical thinking of santri. As a traditional Islamic educational institution, pesantren has a significant role in shaping the character and intellectual abilities of santri. This research uses a qualitative approach with an in-depth case study method, examining the implementation and effectiveness of Bahtsul Masail in santri education. Primary data were collected through in-depth interviews with pesantren managers, teachers, and santri, as well as participatory observation and documentation analysis related to Bahtsul Masail practices. The results showed that effective Bahtsul Masail management can facilitate the development of santri's critical thinking skills through debate and discussion, allowing them to question, criticize, and evaluate various perspectives of Islamic law. The findings highlight the importance of structural and pedagogical arrangements in the implementation of Bahtsul Masail, as well as how good management can integrate the development of intellectual skills in the pesantren curriculum. This research provides insights for pesantren managers in designing educational strategies that support the development of critical thinking skills, which are relevant in today's global era.